Perceptions on epilepsy stigma among attendants of patients other than epilepsy - M Nagarathnam; S A. A. Latheef (Journal of Dr. NTR University of Health Sciences, 2018)
Background: Stigma is an important contributor for epilepsy. In India, most studies on epilepsy stigma were carried out using knowledge, attitude, and practice questionnaires. Of the four studies which used stigma scale, only three studies investigated up to 50 healthy subjects and were of eastern and western-central India; however, representation is lacking from south India. Perceptions on stigma vary by region and cultural group. Aim: To study the perceptions among attendants of patients other epilepsy. Materials and Methods: In a prospective observational study, 170 healthy attendants of patients other than epilepsy belonging to south India were recruited and their perceptions on epilepsy stigma were documented. Results: Mean age of the subjects was 34.39 ± 11.49 years. The mean score of epilepsy stigma was 20.06 ± 13.66. Majority of the subjects had mild epilepsy stigma perception (83.6%). No significant difference in epilepsy stigma score was observed with respect to gender, age groups, religion, and marital status. Higher epilepsy stigma score was observed in rural, less educated, and low income groups. In regression analysis, family income (standardized beta = −0.201, P < 0.01) and occupation (standardized beta = −0.174, P < 0.05) were found to be the significant predictors of epilepsy stigma. Conclusions: The results suggest that, to reduce the stigma of epilepsy among the public, socioeconomic and educationally disadvantaged groups should be given priority for destigmatization campaigns.